Gesture comprehension in persons with aphasia - Kumar, Santhosh; S P, Goswami (Journal of All India Institute of Speech and Hearing, 2013)
The literature postulates impairment in comprehending gesture in persons with aphasia. There are very limited tests available in Indian context for assessing gesture comprehension. Hence, the present study was planned. The study was carried out in two phases. The first phase was development of the test stimuli and the second phase was to administer the test on persons with aphasia. Thirty neuro-typical adults and ten persons with aphasia (5 Broca’s aphasia and 5 global aphasia) participated in the study. It was noticed that there was a significant difference between the performance of neuro-typical adults and persons with aphasia.